2013
DOI: 10.1039/c3tc31130a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent materials for pH sensing and imaging based on novel 1,4-diketopyrrolo-[3,4-c]pyrrole dyes

Abstract: Fluorescent pH-sensors based on 1,4-diketopyrrolo-[3,4-c]pyrrole indicator dyes are presented. Their key advantages are excellent suitability for fluorescence imaging and tunability of the sensitive range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 52 publications
0
51
0
Order By: Relevance
“…For example, five-membered heterocycles are present in more than hundred drugs available in the market and approximately thousands of heterocyclic derivatives are under clinical trials [37]. Apart from this, they have also been known for their catalytic [38,39], fluorescent [40][41][42], and dying properties [43,44].…”
Section: Five-membered Ring Compoundsmentioning
confidence: 99%
“…For example, five-membered heterocycles are present in more than hundred drugs available in the market and approximately thousands of heterocyclic derivatives are under clinical trials [37]. Apart from this, they have also been known for their catalytic [38,39], fluorescent [40][41][42], and dying properties [43,44].…”
Section: Five-membered Ring Compoundsmentioning
confidence: 99%
“…Low solubility prevents the dyes from application as indicators in optical sensors. We previously demonstrated that the dyes are pH-sensitive due to the deprotonation of the lactam nitrogen [29,34]. Modification of the phenyl rings with bulky substituents rendered the pigments soluble in organic solvents and polymers and the pH sensitivity was preserved.…”
Section: Synthesismentioning
confidence: 99%
“…So far only a few applications of DPPs as fluorescent probes are found in the literature [29,[44][45][46]. The new DPP-based pH indicators were shown to be highly promising for application in optical pH and carbon dioxide sensors [29,34]. Particularly, dual emission from the protonated and deprotonated forms enabled ratiometric read-out, but the emission from the deprotonated form was much weaker than that of the protonated form ( prot ≈ 1 and deprot ≈ 0.1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations